The emerging role of community sentinel surveillance in the understanding of the clinical features and epidemiology of acute Mycoplasma pneumoniae infection. (8th January 2014) - Moore, C.; Perry, M.; Cottrell, S.; Raoult, D.
Abstract Retrospective analysis of 3984 test results for the detection of Mycoplasma pneumoniae performed between 2009 and 2013 in Wales was undertaken. Analysis of the clinical presentation of positive cases suggested that mild respiratory infection was common in the community and appeared to coincide with increased hospitalizations. Symptomatic infection was more prevalent in men, with a median age of 22.6 years (range <1–88 years), and 40% of hospitalized cases presented with pneumonia. Inclusion of M. pneumonia nucleic acid amplification tests (NAATs) into routine respiratory NAAT screens will increase the understanding of the epidemiology and clinical spectrum of acute infections in the wider population.